2019
DOI: 10.3390/ijms20194686
|View full text |Cite
|
Sign up to set email alerts
|

Chloride as a Beneficial Macronutrient in Higher Plants: New Roles and Regulation

Abstract: Chloride (Cl−) has traditionally been considered a micronutrient largely excluded by plants due to its ubiquity and abundance in nature, its antagonism with nitrate (NO3−), and its toxicity when accumulated at high concentrations. In recent years, there has been a paradigm shift in this regard since Cl− has gone from being considered a harmful ion, accidentally absorbed through NO3− transporters, to being considered a beneficial macronutrient whose transport is finely regulated by plants. As a beneficial macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 218 publications
2
102
0
Order By: Relevance
“…Plants accumulate Clto macronutrient levels, around 15-50 mg g -1 dry weight (DW), when the external concentration is 1 to 5 mM Cl - (Colmenero-Flores et al, 2019). This range of FIGURe 1 | Overview of the main processes associated to water deficit (WD) resistance.…”
Section: Chloride Membrane Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants accumulate Clto macronutrient levels, around 15-50 mg g -1 dry weight (DW), when the external concentration is 1 to 5 mM Cl - (Colmenero-Flores et al, 2019). This range of FIGURe 1 | Overview of the main processes associated to water deficit (WD) resistance.…”
Section: Chloride Membrane Transportmentioning
confidence: 99%
“…Thus, Clrepresents the dominant inorganic anion in plant cells, with leaf contents that can be similar to those of the macronutrient K + (Franco-Navarro et al, 2016). This accumulation led to better plant performance, the reason why Clhas been recently defined as a beneficial macronutrient (Franco-Navarro et al, 2016;Raven, 2017;Wege et al, 2017;Colmenero-Flores et al, 2019). It is worth highlighting that field assays using durum wheat have shown that soil Cldeficiency caused a number of physiological disorders impairing the growth and yield (Schwenke et al, 2015).…”
Section: Chloride Membrane Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been postulated that proteins regulating potassium uptake channels in the guard cells may be targets for biotechnological strategies against drought (Locascio et al, 2019). The study of chloride homeostasis has often been neglected due to the importance of potassium, which is the major ion in the cytoplasm, but Cl − has a specific beneficial effect in leaf cells by giving rise to larger cells (with higher water storage capacity), lower stomatal conductance and higher mesophyll conductance to CO 2 (Dreyer and Uozumi, 2011;Colmenero-Flores et al, 2019). Therefore, water use efficiency is increased under proper Cl − nutrition.…”
Section: Ion Homeostasis Under Drought Stressmentioning
confidence: 99%
“…Although the occurrence, and mechanism, of inhibitory effects of high, salinizing, Cl − concentrations on glycophytic (crop) plants has received some attention, the main focus in salinity studies has been on the effects of Na + (Raven, 2017; Wege et al , 2017; Colmenero‐Flores et al , 2019; Geilfus, 2019). Recently there has been some emphasis on Cl − at external concentrations between those satisfying the micronutrient requirement in PSII and those inhibiting the growth of glycophytes acting as a ‘beneficial nutrient’ that can increase growth rate (Raven, 2017; Wege et al , 2017; Colmenero‐Flores et al , 2019; Geilfus, 2019). The present paper analyses the quantitative role of Cl − in O 2 production by PSII, as well as other photosynthetic roles such as synthesis and repair of the PSII complex, some of which require high intracellular Cl − concentrations.…”
Section: Introductionmentioning
confidence: 99%